Junk Box Arduino Ten Projects in Upcycled Electronics - Strickland, James R. (Apress : Imprint: Apress, 2016)
We all hate to throw electronics away. Use your 5 volt Arduino and have fun with them instead! Raid your electronics junk box to build the Cestino (Arduino compatible) board and nine other electronics projects, from a logic probe to a microprocessor explorer, and learn some advanced, old-school techniques along the way. Don't have a well-stocked junk box? No problem. Nearly all the components used in these projects are still available (and cheap) at major electronic parts houses worldwide. Junk Box Arduino is the ultimate have-fun-while-challenging-your-skills guide for Arduino hackers who've gone beyond the basic tutorials and are ready for adventures in electronics. You'll build the Cestino (it means recycle bin), and learn how Arduino compatibles actually work, and how to make your own. You'll learn about eight bit ports and binary logic building the Larson (Memorial) Scanner. You'll learn how transistors really work, and how to use them without frying them as you build and use the transistor analyzer. You'll learn about TTL (Transistor-Transistor Logic), and see what the ubiquitous 7400 series logic chips actually do with the TTL chip tester you'll build. You'll understand logic levels and that high does not always equal true because you can see them when you build a simple logic probe. You'll learn how to interface EPROM and EEPROM/FLASH memory as you explore the contents of that old video game or BIOS EPROM. You'll learn how ATA drives communicate by resurrecting that old PATA drive you kept from 10 years ago. You'll build a role playing game dice roller with a two digit, 7 segment display and learn to use Arduino interrupts for pin multiplexing. You'll learn how computers really work by connecting a Z80 microprocessor to memory and peripherals simulated by your Cestino. You'll even learn a little assembly language.< Bonus materials include all the example sketches, the Cestino core and bootloader source code, and links to suppliers for parts and tools.